SENSITIVITAS ETIS DAN PERTIMBANGAN ETIS MAHASISWA AKUNTANSI BERDASARKAN PENDIDIKAN ETIKA AKUNTANSI - Anggi Ayu Septi Kennedy; Lisa Martiah Nila Puspita (Jurnal Akuntansi, 2018)
This study examined the differences between ethical sensitivity and ethical judgement by students based on their knowledge of accounting ethics education. A total of 40 accounting students attended accounting ethics education in University of Bengkulu responded to questionnaire and another 43 students who does not complete an accounting ethics education were included for comparative purpose. Statistical analysis reveals that students who attended an accounting ethics education improved significantly in their ethical sensitivity and ability to made an ethical judgement compared to students who does not attended the accounting ethics education. Females students got more benefit from an accounting ethics education and increased their ability to made ethical judgement compared to male students, but in contrast, between male students and female students who attended accounting ethics education has no difference in terms of their ethical sensitivity.Key words: Ethical sensitivity, ethical judgement, accounting ethics education